209k views
3 votes
Show your work and explain in a full sentence how 4 2-6 is equivalent to 3 8-6.

1 Answer

3 votes

Answer:


4(2)/(6) = 3(8)/(6) = (26)/(6)

Step-by-step explanation:

Given


4(2)/(6) and
3(8)/(6)

Required

Show that they are equivalent

To do this, we simply convert both fractions to either decimal or improper fraction

Using improper fraction


4(2)/(6) = (6 * 4 + 2)/(6)


4(2)/(6) = (24 + 2)/(6)


4(2)/(6) = (26)/(6)


3(8)/(6) = (6 *3+8)/(6)


3(8)/(6) = (18+8)/(6)


3(8)/(6) = (26)/(6)

After converting both to improper fraction, we have:


4(2)/(6) = 3(8)/(6) = (26)/(6)

Hence, both are equivalent

User NCardot
by
5.5k points